Teaching Methodology of Russian Language in Technical Universities (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article delves into the intricacies of the teaching methodology employed in technical universities for instructing the Russian language to students. The focus is on the specialized vocabulary, communicative approach, integrated language skills, practical application in technical contexts, utilization of technological resources, cultural awareness and context, ongoing assessment and feedback, and professional development aspects of the methodology. By examining these key facets, we aim to provide insights into how technical universities equip students with the language skills and communication proficiency necessary for success in their academic and professional endeavors. The comprehensive approach outlined in this article underscores the importance of tailoring language instruction to meet the unique needs of students in technical fields, facilitating their effective communication and future success.